2005
DOI: 10.1002/j.2050-0416.2005.tb00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dark Specialty Malts on Extract Composition and Wort Fermentation

Abstract: Dark specialty malts are important ingredients for the production of several beer styles. These malts not only impart colour, flavour and antioxidative activity to wort and beer, they also affect the course of wort fermentations and the production of flavouractive yeast metabolites. The application of considerable levels of dark malt was found to lower the attenuation, mainly as a result of lower levels of fermentable sugars and amino acids in dark wort samples. In fact, from the darkest caramel malts and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 21 publications
7
42
1
Order By: Relevance
“…The synthesis of both higher alcohols and esters are known to be directly affected by these two parameters. Despite research suggesting that MRPs can affect the activity of enzymes involved in the synthesis of higher alcohols (Modig et al, 2002) and antimicrobial properties of MRPs against a number of microorganisms, to date only one study has reported the effect of dark speciality malts on yeast fermentation and volatile metabolite synthesis (Coghe et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of both higher alcohols and esters are known to be directly affected by these two parameters. Despite research suggesting that MRPs can affect the activity of enzymes involved in the synthesis of higher alcohols (Modig et al, 2002) and antimicrobial properties of MRPs against a number of microorganisms, to date only one study has reported the effect of dark speciality malts on yeast fermentation and volatile metabolite synthesis (Coghe et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Work by Coghe et al (2005) showed a correlation between increasing wort colour and decreasing rate of ethyl acetate formation, while isoamyl acetate production was completely inhibited when fermenting dark malt wort. On the other hand, they showed that the synthesis of higher alcohols was not seen to be affected by dark-coloured wort.…”
Section: Introductionmentioning
confidence: 98%
“…Three synthetic fermentative media were used; they differed in their levels of sugar and nitrogen, pH, osmotic pressure, and anaerobic growth factors in order to reflect the main changes of fermentation medium between brewing, baking, and wine-making contexts (see Table 2). Maltose is the main available sugar in wort and dough (14,44), and yet most of the strains used in wine making cannot assimilate it (42). Moreover, previous work shows that the presence of maltose in the medium could affect glycolysis even for strains lacking the maltose permease (52).…”
Section: Methodsmentioning
confidence: 99%
“…Yeast chronological aging is studied almost exclusively on synthetic complete minimal (SC) medium, which has high ammonium sulfate levels, and is weakly buffered against changes in pH compared to natural yeast substrates (Coghe et al 2005;Sanchez 2008;Garde-Cerdán et al 2011;Oliva et al 2011) and standard yeast peptone (YP) medium (Weinberger et al 2010). SC medium is used in chronological aging studies because yeast grown to saturation in this medium arrest efficiently in stationary phase, with most if not all cells remaining quiescent until plated to fresh medium (Longo and Fabrizio 2012).…”
mentioning
confidence: 99%
“…But in nature, S. cerevisiae seems particularly well-adapted to high-sugar environments, with many yeast substrates containing well over 10% sugar by weight. For reference, brewing wort typically ranges from 8 to 12% w/v sugar (Coghe et al 2005), tree saps contain as much as 16% sugar (Sanchez 2008), and grapes can contain .20% sugar Oliva et al 2011). All of these substrates are favored environments of S. cerevisiae.…”
mentioning
confidence: 99%